Measurement and analysis of water/oil multiphase flow using electrical capacitance tomography sensor - Mohamad, Elmy Johana; Marwah, Omar Mohd Faizan; Mohd Muji, Siti Zarina; R.A., Rahim; H.L.M., Ameran; M.H.F., Rahiman (Elsevier Ltd., 2016)
The paper investigates the capability of using a portable 16-segmented Electrical Capacitance Tomo-graphy (ECT) sensor and a new excitation technique to measure the concentration profile of water/oil multiphase flow. The concentration profile obtained from the capacitance measurements is capable of providing images of the water and oil flow in the pipeline. The visualization results deliver information regarding the flow regime and concentration distribution of the multiphase flow. The information is able to help in designing process equipment and verifying the existing computational modeling and simu-lation techniques.